Quantitative Characterization of Grouting Stones for Drilling with Pre-stressed Concrete Pile Cased Pile. Issue 2 (January 2021) - Hou, Zhenkun; Tang, Mengxiong; Hu, Hesong; Lin, Zegeng; Chen, Hang; Liu, Chunlin
Abstract: The bearing property of Drilling with pre-stressed concrete pile cased pile is closely related to the grouting effect on the pile side. Based on the 3D scanner, the characteristics of the grouting stone body was quickly obtained with large area and high resolution through high-speed laser scanning measurement technology and extrapolation multi-frequency phase-shift laser grating technology, and the following conclusion was drawn: the quantitative characterization method of grouting rock mass based on the 3D scanner is stable and reliable, its workload is small, data density is large, test process is accurate and fast, and it overcomes the shortcomings of traditional manual measurement; under the condition of same elevation, the thickness of grout decreases as the distance away from the coordinate origin increases, namely in the same horizontal plane, the farther the horizontal distance away from the grout outlet position, the smaller the grout thickness; the greater the elevation, as the horizontal distance away from the grout outlet increases, the larger the decrease rate of grout thickness, the faster the grout thickness decreases; when the horizontal distance away from the grout outlet position is constant, as the elevation increases, the grout thickness gradually decreases.